2003
DOI: 10.2320/matertrans.44.211
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of the Structural Alignment in Fe-0.4C Alloy Transformed in High Magnetic Field

Abstract: Structural alignment in Fe-0.4C alloy transformed in high magnetic field has been evaluated by quantitative microscopy analysis. An aligned two-phase structure is formed in high magnetic field by austenite to ferrite transformation during slow cooling. Ferrite grains are elongated and connected with each other along the direction of magnetic field. The degree of alignment can be evaluated by measuring the number of intersections between test lines and ferrite/austenite phase boundaries. Results of measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…2,3) However, this kind of structure was not found in pure Fe and Fe-0.8C alloy through microstructural observation. For pure Fe, the reason can be attributed to that the magnetization at transformation temperature is small and the demagnetization field is also weak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3) However, this kind of structure was not found in pure Fe and Fe-0.8C alloy through microstructural observation. For pure Fe, the reason can be attributed to that the magnetization at transformation temperature is small and the demagnetization field is also weak.…”
Section: Resultsmentioning
confidence: 99%
“…Fe-C alloy is an ideal system to show the magnetic field effect since in this system, austenite (fcc structure) is a paramagnetic phase and ferrite (bcc structure) is a ferromagnetic phase below Curie temperature (T c , 770 C). Elongated and aligned microstructures formed by solid/solid transformations in a high magnetic field have been reported by ferrite transformation [1][2][3][4][5] and reverse transformation from martensite. 6,7) Kakeshita et al 8) have investigated the effects of magnetic field on martensite transformation temperature (M s ) in several Fe-based alloys and found that M s increases in a high magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…4, austenite grains formed upon heating were aligned along the direction of the applied field. Subsequently, Ohtsuka et al [52][53][54] reported the alignment of ferrite grains in the forward transformation in a field of 10 T. The alignment occurred more readily when the alloy was cooled slowly, which may indicate that the magnetic interaction between the two ferrite grains played an essential role during the transformation at a small undercooling at which the chemical driving force for the transformation is small.…”
Section: Precipitation and Ordering Transformation In Iron Alloysmentioning
confidence: 99%
“…transformation after a prior hot-rolling in region. It was made clear by Ohtsuka et al that some conditions have to be satisfied for the elongation and alignment of ferrite grains, 3,6,11,12) that is, the degree of elongation of ferrite grains increases with (1) increasing magnetic field strength, (2) decreasing austenite grain size, (3) decreasing driving force for transformation in Fe-C alloys. However, the conditions for the structural elongation and alignment for lath martensite to austenite reverse-transformation have never been shown.…”
Section: Introductionmentioning
confidence: 99%
“…9,10) For austenite () to ferrite () diffusional transformation in Fe-based alloys, it was shown by Ohtsuka et al that the grains are elongated and aligned along the direction of applied magnetic field. 3,6,11,12) Later Shimotomai et al 13) showed that grains are aligned during ! transformation after a prior hot-rolling in region.…”
Section: Introductionmentioning
confidence: 99%